4D Printing: The Shape-Morphing in Additive Manufacturing - Piedade, Ana P. (2019)
3D printing of polymers can now be considered as a common processing technology for the development of biomaterials. These can be constituted out of polymeric abiotic material alone or can be co-printed with living cells. However, the adaptive and shape-morphing characteristics cannot be developed with the rigid, pre-determined structures obtained by 3D printing. In order to produce functional engineered biomaterials, the dynamic properties/characteristics of the living cells must be attained. 4D printing can be envisaged as a route to achieve these goals. This paper intends to give a brief review of the pioneer 4D printing research that has been developed and to present an insight into future research in this field.